CORRELATION BETWEEN HELICOBACTER PYLORI AND TYPE 2 DIABETES IN KIRKUK-IRAQ - Muhsen A. Sulyman; Mohammed Abdul-Aziz Kadir; Suhaila Shamseeldeen Tahir (Scholar Express Journals, 2022)
Background: Helicobacter pylori is a common bacterial pathogen of human beings, causes different gastric problems as ulcers, tumors and inflammation as gastritis. The chronic inflammation may have impact on glucose and lipid absorption. Diabetes mellitus is characterized by a high level of blood glucose Glycated hemoglobin (HBA1C) The objective of the study is to show the relationship between H. pylori and diabetes mellitus. Methods: The study was conducted on 116 patients with type 2 diabetes mellitus who attended K1 hospital in North Oil Company, Kirkuk, and 80 healthy individuals. H. pylori was detected by using H. pylori antigen rapid test in feces. Estimation of sugar was done by a high level of blood glucose and glycated hemoglobin (HBAIC) using a fully smart automated clinical chemistry analyzer. Results: This study showed the frequency of H. pylori in diabetic patients was 28.4%, the highest rate was among 30-39 years, employees, and illiterates. The lowest was among university-educated level and no cases seen among students. Conclusions: Higher rate of H. pylori among patients with diabetes may indicate a strong link between H. pylori and Type 2 diabetes mellitus
Keywords: Helicobacter pylori; Type 2 diabetes; K1 hospital; Kirkuk